A kind of 18-core silver nanocage microbeads and its preparation method and application
By constructing 18-core silver nanocage microbeads, enriching and secondary encapsulating 99Tc with its high selectivity and large adsorption capacity, the problem of difficulty in efficient enrichment and encapsulation of 99Tc in the prior art is solved, and the crystallization performance of the silver nanocage is improved, achieving the application prospects in radioactive nuclear spent fuel post-treatment.
Patent Information
- Application Number
- CN202211064723.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-08-31
AI Technical Summary
The prior art is difficult to quickly and efficiently enrich and secondary encapsulate radioactive contaminants 99Tc in aqueous solutions, and silver nanocages are prone to crystallization, limiting their range in large-scale industrial applications.
A preparation method is used to construct octadecano-core silver nanocage microbeads, which involves mixing silver trifluoromethanesulfonate, tert-butylyne silver, perrhenic acid or pertechnetic acid in a specific proportion to form a solution, and then reacting at room temperature to obtain octadecano-core silver nanocage and mixing it with sodium alginate monomer and calcium chloride to form a microbead structure.
The rapid and efficient enrichment and secondary packaging of 99Tc in aqueous solution was achieved, which inhibited the overflow of 99Tc and metal ions, maintained high stability in aqueous solution, improved the crystallization performance of silver nanocages, and expanded its industrial application range.
Smart Images

Figure CN115322401B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a metal nanocage microbead and a preparation method and application thereof, and in particular to a silver nanocage microbead constructed by 18-nuclear silver nanocages, a preparation method of the 18-nuclear silver nanocage microbead, and application of the 18-nuclear silver nanocage microbead in encapsulating radioactive 99 The application of Tc belongs to the technical field of radioactive nuclear spent fuel post-processing. Background Art
[0002] Over the past 70 years, it is estimated that 235 U or 239 The fission of Pu produced about 400 tons of 99 Tc, most of which are awaiting final disposal, are a major environmental concern. 99 For example, the half-life of the beta rays it emits is 2.13×10 5 Year, 99 Tc is mainly present in the +7 oxidation state under oxidation or acidic reduction conditions. 99 TcO4 - The form exists because 99 TcO4 - Its non-complexing nature, high water solubility and high stability make it extremely fluid in the natural environment, and it can be transported underground at almost the same speed as groundwater. 99 Tc can be converted into volatile Tc2O7 during the vitrification process, which will cause great radioactive material volatilization pollution. Therefore, it is necessary to develop new technologies and new materials to quickly and effectively absorb 99 TcO4 - , which is of great significance for waste separation and pollutant remediation.
[0003] Traditional commercial resin materials, cationic MOFs materials and silver nanocages are all materials that can adsorb anions. Among them, traditional commercial resin materials and cationic MOFs materials adsorb anions by ion exchange. The principle of silver nanocage adsorption of anions is different from that of traditional commercial resin materials and cationic MOFs materials. The energy levels of the 5s and 5p orbitals of the silver ions that constitute the silver nanocage are close to the energy level of the 4d orbital. Therefore, geometrically adjacent silver ions can easily form silver-silver interactions with each other, making the constructed silver nanocages easy to carry a large amount of positive charge, and it is very easy to use the principle of charge balance to enrich negatively charged anions and permanently encapsulate them in the confined space of the silver nanocage to balance their own charge. Therefore, the functional silver nanoclusters with anion template induction effect not only have excellent nanocage confinement effect, but also can enrich and encapsulate a series of polyhedral anions, and are potential anion adsorption materials. In addition, silver ions are a soft acid, which has excellent binding ability for most of the coordinated atoms in the ligand, and has adjustable charge density, pore size and easy modification of crystallization. They have received extensive attention in recent years. For example:
[0004] (1) In 2001, Mingos et al. first reported tetradecanuclear silver (I) alkynyl clusters encapsulating spherical halide ions (A facile template approach to high-nuclearity silver (I) alkynyl clusters. Angew. Chem. Int. Ed., 2009, 48 5363-5365);
[0005] (2) In 2009, Wang Quanming's research group first encapsulated carbon dioxide from the air into nineteen-nuclear silver clusters in the form of carbonate by controlling the synthesis conditions (High-nuclearity silver clusters templated by carbonates generated from atmospheric carbon dioxide fixation. J. Am. Chem. Soc., 2009, 131 3422-3423);
[0006] (3) In 2020, Liu Kuangguan's research group converted tetrahedral AsO4 3-Encapsulated into a twenty-two-nucleus silver nanocage (Investigation of the Effect of a Mixed-Ligand on the Accommodation of a Templated Molecule into the Structure of High-Nucleus Silver Clusters Inorg. Chem. 2020, 59, 2248-2254).
[0007] Although there are a large number of literatures reporting on the encapsulation of various anions in silver cages, there are no reports on the selective enrichment of anions by silver cages and the encapsulation of nuclear waste pollutant anions by silver cages.
[0008] In addition, since silver cages are easily crystallized materials, their use in large-scale industrial applications is limited. If the easily crystallized silver cages can be constructed into microbeads, the crystallization properties of the silver cages will be effectively improved, expanding their application range in large-scale industrial applications.
[0009] Therefore, how to develop a method that can efficiently enrich radioactive pollutants in aqueous solutions? 99 Tc and achieve radioactive contaminants 99 Silver nanocage microbeads with secondary Tc encapsulation have become an urgent problem to be solved in this field. Summary of the invention
[0010] The purpose of the present invention is to provide a method for rapidly and efficiently enriching radioactive pollutants in aqueous solutions. 99 Tc can also achieve radioactive contaminants 99 Tc secondary encapsulated silver nano cage micro beads and a preparation method of the silver nano cage micro beads.
[0011] In order to achieve the above object, the present invention adopts the following technical solution:
[0012] A method for preparing 18-core silver nanocage microbeads, characterized in that it comprises the following steps:
[0013] 1. Preparation of 18-core silver nanocages
[0014] (1) silver trifluoromethanesulfonate, methanol and dichloromethane are mixed in a ratio of 50-53 mg: 2-4 mL: 2-4 mL or a larger ratio, and reacted at room temperature to obtain solution A;
[0015] (2) adding tert-butyl silver acetylide to solution A, wherein the mass ratio of the added amount of tert-butyl silver acetylide to the silver trifluoromethanesulfonate in step (1) is 1:1-2, and reacting at room temperature to obtain solution B;
[0016] (3) adding perrhenic acid or pertechnetate to solution B, wherein the mass ratio of the added amount of perrhenic acid or pertechnetate to the silver trifluoromethanesulfonate in step (1) is 1:1-2, and reacting at room temperature to obtain octadecanoic silver nanocages;
[0017] 2. Construction of Silver Nanocage Beads
[0018] The octadecenoic silver nanocages, sodium alginate monomers and calcium chloride obtained in step 1 are mixed, and then added into polyacrylic acid, wherein the mass ratio of the octadecenoic silver nanocages, sodium alginate monomers, calcium chloride and polyacrylic acid is 1:2:5:2, to obtain silver nanocage microbeads.
[0019] Preferably, in step (1), the reaction time is 5 to 10 minutes.
[0020] Preferably, in step (2), the reaction time is 5 to 10 minutes.
[0021] Preferably, in step (3), the reaction time is 60 to 120 minutes; the perrhenic acid is potassium perrhenate or ammonium perrhenate; and the pertechnetate is potassium pertechnetate or ammonium pertechnetate.
[0022] An octa-nuclear silver nanocage microbead, characterized in that it is prepared by the above method, and the octa-nuclear silver nanocage microbead can be used to encapsulate radioactive 99 Tc.
[0023] The present invention is beneficial in that:
[0024] (1) The 18-nuclear silver nanocage prepared by the present invention 99 Tc has strong selectivity, high adsorption capacity, and fast adsorption speed, and can quickly and efficiently enrich radioactive pollutants in aqueous solutions. 99 T;
[0025] (2) The 18-core silver nanocage microbeads constructed by the present invention can achieve radioactivity 99 Tc secondary encapsulation can maximally inhibit the presence of 99 The overflow of Tc and metal ions makes 99 Tc and metal ions maintain long-term high stability in aqueous solution;
[0026] (3) The method for preparing 18-core silver nanocages provided by the present invention can be completed at room temperature, is easy to crystallize, and is green and environmentally friendly;
[0027] (4) The method for preparing 18-core silver nanocages provided by the present invention has good biocompatibility and can fully meet environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a structural diagram of the 18-core silver nanocage prepared by the present invention;
[0029] Figure 2 The 18-nuclear silver nanocage prepared in Example 1 is PO4 3- 、SO4 2- 、ReO4 - and NO3 - The test results of the removal rate of these four ions are shown in the figure;
[0030] Figure 3 The 18-nuclear silver nanocage (abbreviated as Ag) prepared in Example 1 is Mg-Al-LDH, NDTB-1, Y2(OH)5Cl, Yb3O(OH)6Cl and 18 ) of ReO4 - Adsorption capacity test result diagram;
[0031] Figure 4 The ReO4 of the 18-core silver nanocage prepared in Example 1 - Adsorption rate test result diagram;
[0032] Figure 5 This is a P-XRD test result diagram of 18-core silver nanocage microbeads constructed using the 18-core silver nanocage prepared in Example 1;
[0033] Figure 6 The 18-core silver nanocage microbeads prepared in Example 1 were used to encapsulate ReO4 - The ICP-OES test results obtained later. DETAILED DESCRIPTION
[0034] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0035] 1. Preparation of 18-core silver nanocages
[0036] The method for preparing octa-core silver nanocage provided by the present invention mainly comprises the following steps:
[0037] (1) silver trifluoromethanesulfonate, methanol and dichloromethane were mixed in a ratio of 50-53 mg: 2-4 mL: 2-4 mL, and reacted at room temperature for 5-10 min to obtain a colorless transparent solution, which was recorded as solution A;
[0038] (2) adding tert-butyl silver acetylide to solution A, wherein the mass ratio of the added amount of tert-butyl silver acetylide to the silver trifluoromethanesulfonate in step (1) is 1:1-2, and reacting at room temperature for 5-10 minutes to obtain a colorless transparent solution, which is recorded as solution B;
[0039] (3) adding perrhenic acid or pertechnetate to solution B, wherein the mass ratio of the added amount of perrhenic acid or pertechnetate to the silver trifluoromethanesulfonate in step (1) is 1:1-2, and reacting at room temperature for 60-120 minutes to obtain 18-nuclear silver nanocages.
[0040] Example 1
[0041] 50 mg of silver trifluoromethanesulfonate, 2 mL of methanol and 2 mL of dichloromethane were mixed and reacted at room temperature for 5 min to obtain a colorless transparent solution, which was recorded as solution A.
[0042] 50 mg of tert-butyl silver acetylene (tert-butyl silver acetylene: silver trifluoromethanesulfonate = 1:1) was added to solution A and reacted at room temperature for 8 minutes to obtain a colorless transparent solution, which was recorded as solution B.
[0043] 50 mg of potassium perrhenate was added to solution B and reacted at room temperature for 60 min to obtain 18-nuclear silver nanocages with the structure shown in FIG. Figure 1 shown.
[0044] Example 2
[0045] 51 mg of silver trifluoromethanesulfonate, 2 mL of methanol and 2 mL of dichloromethane were mixed and reacted at room temperature for 5 min to obtain a colorless transparent solution, which was recorded as solution A.
[0046] 34 mg of tert-butyl silver acetylene (tert-butyl silver acetylene: silver trifluoromethanesulfonate = 1:1.5) was added to solution A and reacted at room temperature for 5 minutes to obtain a colorless transparent solution, which was recorded as solution B.
[0047] 34 mg of ammonium perrhenate was added to solution B and reacted at room temperature for 80 min to obtain 18-nuclear silver nanocages with the structure shown in FIG. Figure 1 shown.
[0048] Example 3
[0049] 52 mg of silver trifluoromethanesulfonate, 4 mL of methanol and 4 mL of dichloromethane were mixed and reacted at room temperature for 10 min to obtain a colorless transparent solution, which was recorded as solution A.
[0050] 26 mg of tert-butyl silver acetylide (tert-butyl silver acetylide: silver trifluoromethanesulfonate = 1:2) was added to solution A and reacted at room temperature for 8 minutes to obtain a colorless transparent solution, which was recorded as solution B.
[0051] 26 mg of potassium pertechnetate was added to solution B and reacted at room temperature for 100 min to obtain 18-nuclear silver nanocages with the structure shown in FIG. Figure 1 shown.
[0052] Example 4
[0053] 53 mg of silver trifluoromethanesulfonate, 4 mL of methanol and 4 mL of dichloromethane were mixed and reacted at room temperature for 10 min to obtain a colorless transparent solution, which was recorded as solution A.
[0054] 53 mg of tert-butyl silver acetylene (tert-butyl silver acetylene: silver trifluoromethanesulfonate = 1:1) was added to solution A and reacted at room temperature for 10 min to obtain a colorless transparent solution, which was recorded as solution B.
[0055] 53 mg of ammonium pertechnetate was added to solution B and reacted at room temperature for 120 min to obtain 18-nuclear silver nanocages with the structure shown in FIG. Figure 1 shown.
[0056] 2. Detection of ion selectivity of 18-core silver nanocages, ReO4 - Adsorption capacity and ReO4 - Adsorption speed
[0057] The silver nanocages prepared in Example 1, Example 2, Example 3 and Example 4 are all 18-nuclear silver nanocages, having the same structure and properties. The 18-nuclear silver nanocage prepared in Example 1 is used as a representative to detect the ion selectivity, ReO4 - Adsorption capacity and ReO4 - Adsorption speed.
[0058] 1. Ion selectivity
[0059] The 18-core silver nanocages prepared in Example 1 were used to adsorb PO4 in the solution. 3- 、 SO4 2- 、ReO4 - and NO3 - , the 18-core silver nanocage was tested for PO4 3- 、SO4 2- 、ReO4 - and NO3 - The removal rates of these four ions are shown in the test results. Figure 2 .
[0060] Depend on Figure 2 It can be seen that the 18-core silver nanocage prepared in Example 1 has a strong affinity for PO4 3- 、SO4 2- 、ReO4 - and NO3 - The removal rates of ReO4 were 68%, 43%, 80% and 10% respectively. - The removal effect is best.
[0061] It can be seen that the 18-core silver nanocage prepared by the present invention has a strong affinity for ReO4 - Has higher selectivity.
[0062] 2. ReO4 - Adsorption capacity
[0063] The 18-core silver nanocage (denoted as Ag) prepared in Example 1 18 ) Adsorption of ReO4 in solution - , detecting the ReO4 - Adsorption capacity, test results see Figure 3 .
[0064] Mg-Al-LDH, NDTB-1, Y2(OH)5Cl and Yb3O(OH)6Cl were used to adsorb ReO4 in solution respectively. - , detection of ReO4 in Mg-Al-LDH, NDTB-1, Y2(OH)5Cl and Yb3O(OH)6Cl - Adsorption capacity, test results see Figure 3 .
[0065] Depend on Figure 3 It can be seen that Mg-Al-LDH, NDTB-1, Y2(OH)5Cl, Yb3O(OH)6Cl and Ag 18 ReO4 - The adsorption capacities are 130.2 mg / g, 49.4 mg / g, 87.3 mg / g, 48.6 mg / g and 480 mg / g, respectively. 18 ReO4 - The adsorption capacity of ReO4 is the largest and significantly higher than that of Mg-Al-LDH, NDTB-1, Y2(OH)5Cl and Yb3O(OH)6Cl. - Adsorption capacity.
[0066] It can be seen that the 18-core silver nanocage prepared by the present invention has a strong affinity for ReO4 - It has a large adsorption capacity.
[0067] 3. ReO4 - Adsorption speed
[0068] The 18-nuclear silver nanocage prepared in Example 1 was used to adsorb ReO4 in the solution. - , detect the adsorption of ReO4 by the 18-core silver nanocage - The speed of the test results is shown in Figure 4 .
[0069] Depend on Figure 4 It can be seen that the 18-core silver nanocage prepared in Example 1 completed the ReO4 - adsorption.
[0070] It can be seen that the 18-core silver nanocage prepared by the present invention has a faster ReO4 - Adsorption speed.
[0071] 3. Construction of 18-core silver nanocage microbeads
[0072] The 18-nuclear silver nanocage prepared by the present invention is fixed in a double cross-linked network with good biocompatibility and biodegradability to construct the 18-nuclear silver nanocage microbeads.
[0073] Taking the 18-core silver nanocage prepared in Example 1 as an example, the process of constructing the 18-core silver nanocage microbeads is as follows:
[0074] The octadecenoic silver nanocages, sodium alginate monomers and calcium chloride prepared in Example 1 were mixed and then added to polyacrylic acid. The mass ratio of the octadecenoic silver nanocages, sodium alginate monomers, calcium chloride and polyacrylic acid was 1:2:5:2. The octadecenoic silver nanocage microbeads were obtained by uniform mixing, which were recorded as Ag18@PAC.
[0075] The constructed Ag18@PAC was tested by polycrystalline X-ray diffractometer (P-XRD). Figure 5 .
[0076] Depend on Figure 5 It can be seen that eighteen-core silver nanocage microbeads were successfully prepared.
[0077] 4. Encapsulation of ReO4 with 18-core silver nanocage microbeads -
[0078] The octa-core silver nanocage microbeads prepared above were used to encapsulate ReO4 at different pH values. - After packaging, the inductively coupled plasma optical emission spectrometer (ICP-OES) was used for detection. The test results are shown in Figure 6 .
[0079] Depend on Figure 6 It can be seen that the 18-core silver nanocage microbeads have achieved the goal of - Secondary packaging.
[0080] In summary, the 18-core silver nanocage prepared by the present invention has a strong affinity for ReO4 - It has high selectivity, large adsorption capacity and fast adsorption speed; the 18-core silver nanocage microbeads constructed by the 18-core silver nanocage can encapsulate ReO4 for the second time. - .
[0081] ReO4 - It is radioactive 99 The laboratory analogue of Tc, so it can be determined that the 18-core silver nanocage microbeads prepared by the present invention have a99 Tc has high selectivity, large adsorption capacity and fast adsorption speed, and can achieve radioactive 99 Tc secondary encapsulation can maximally inhibit the presence of 99 The overflow of Tc and metal ions makes 99 Tc and metal ions maintain long-term high stability in aqueous solution. That is to say, the 18-core silver nanocage microbeads constructed by the present invention have good application prospects in the post-processing of radioactive nuclear spent fuel.
[0082] It should be noted that the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing octa-nuclear silver nanocage microbeads, characterized in that: The following steps are involved:
1. Preparation of 18-core silver nanocages (1) silver trifluoromethanesulfonate, methanol and dichloromethane are mixed in a ratio of 50-53 mg: 2-4 mL: 2-4 mL or a larger ratio, and reacted at room temperature to obtain solution A; (2) adding tert-butyl silver acetylide to solution A, wherein the mass ratio of the added amount of tert-butyl silver acetylide to the silver trifluoromethanesulfonate in step (1) is 1:1-2, and reacting at room temperature to obtain solution B; (3) adding perrhenic acid or pertechnetate to solution B, wherein the mass ratio of the added amount of perrhenic acid or pertechnetate to the silver trifluoromethanesulfonate in step (1) is 1:1-2, and reacting at room temperature to obtain octadecanoic silver nanocages; 2. Construction of Silver Nanocage Beads The octadecenoic silver nanocages, sodium alginate monomers and calcium chloride obtained in step 1 are mixed, and then added into polyacrylic acid, wherein the mass ratio of the octadecenoic silver nanocages, sodium alginate monomers, calcium chloride and polyacrylic acid is 1:2:5:2, to obtain silver nanocage microbeads.
2. The method for preparing 18-nuclear silver nanocage microbeads according to claim 1, characterized in that: In step (1), the reaction time is 5 to 10 minutes.
3. The method for preparing 18-nuclear silver nanocage microbeads according to claim 1, characterized in that: In step (2), the reaction time is 5 to 10 minutes.
4. The method for preparing 18-nuclear silver nanocage microbeads according to claim 1, characterized in that: In step (3), the reaction time is 60 to 120 minutes.
5. The method for preparing 18-nuclear silver nanocage microbeads according to claim 1, characterized in that: In step (3), the perrhenic acid is potassium perrhenate or ammonium perrhenate.
6. The method for preparing 18-nuclear silver nanocage microbeads according to claim 1, characterized in that: In step (3), the pertechnetate used is potassium pertechnetate or ammonium pertechnetate.
7. An octa-nuclear silver nanocage microbead, characterized in that: Prepared by the method according to any one of claims 1 to 6.
8. The 18-nuclear silver nanocage microbeads of claim 7 are used to encapsulate radioactive 99 Application of Tc.
Citation Information
Patent Citations
Preparation method for cage-shaped nanometer gold-silver alloy suitable for being used as organic dye catalyst
CN105618786A
Use of assembled N-Ag-TiO2-ZnO nano cage in methylyellow degradation reaction under visible light
CN108554436A